Poverty in times of crisis - Alexander Ahammer; Stefan Kranzinger (Johannes Kepler University of Linz, Department of Economics, 2017)
This paper evaluates the impact of a large macroeconomic shock on poverty. In particular, we use longitudinal data from the European Survey on Income and Living Conditions (EU-SILC) comprising almost two million individuals from 29 European countries in order to quantify changes in poverty transition patterns caused by the 2007 global financial crisis. Because the crisis was largely unforeseeable, it provides an appealing natural experiment allowing us to isolate the causal effect of a substantial macroeconomic shock on poverty. Employing semiparametric mixed discrete time survival analysis, we find that conditional poverty entry hazards increased temporarily by 13.4% during the crisis, while post-crisis they are estimated to be 15.7% lower than before. Not only entry hazards have decreased, also conditional exit hazards are estimated to be 31.4% lower post-crisis compared to before. Ceteris paribus, the crisis therefore has made it more difficult to slip into poverty, yet those who were already poor face substantially lower prospects to escape. Exploring determinants of poverty transitions, we find that being retired, having a permanent job, owning one's dwelling instead of renting it, age, marital status, and household size are the most important protective factors against poverty. Finally, we show that mostly a housing cost overburden seems to be responsible for the persistence of poverty.
Keywords: D31; I32; 330; poverty transitions; financial crisis; entry and exit rates